Why not just Google it? An assessment of information literacy skills in a biomedical science curriculum - Kingsley, Karl (BioMed Central, 2011)
BACKGROUND: Few issues in higher education are as fundamental as the ability to search for, evaluate, and synthesize information. The need to develop information literacy, the process of finding, retrieving, organizing, and evaluating the ever-expanding collection of online information, has precipitated the need for training in skill-based competencies in higher education, as well as medical and dental education. METHODS: The current study evaluated the information literacy skills of first-year dental students, consisting of two, consecutive dental student cohorts (n = 160). An assignment designed to evaluate information literacy skills was conducted. In addition, a survey of student online search engine or database preferences was conducted to identify any significant associations. Subsequently, an intervention was developed, based upon the results of the assessment and survey, to address any deficiencies in information literacy. RESULTS: Nearly half of students (n = 70/160 or 43%) missed one or more question components that required finding an evidence-based citation. Analysis of the survey revealed a significantly higher percentage of students who provided incorrect responses (n = 53/70 or 75.7%) reported using Google as their preferred online search method (p < 0.01). In contrast, a significantly higher percentage of students who reported using PubMed (n = 39/45 or 86.7%) were able to provide correct responses (p < 0.01). Following a one-hour intervention by a health science librarian, virtually all students were able to find and retrieve evidence-based materials for subsequent coursework. CONCLUSIONS: This study confirmed that information literacy among this student population was lacking and that integration of modules within the curriculum can help students to filter and establish the quality of online information, a critical component in the training of new health care professionals. Furthermore, incorporation of these modules early in the curriculum may be of significant value to other dental, medical, health care, and professional schools with similar goals of incorporating the evidence base into teaching and learning activities.